ASME 5th International Conference on Nanochannels, Microchannels, and Minichannels 2007
DOI: 10.1115/icnmm2007-30104
|View full text |Cite
|
Sign up to set email alerts
|

Passive Heat Transfer Enhancement in Microchannels Using Wall Features

Abstract: The two important considerations in the design of a heat exchanger are — the total heat transfer rate and the allowable pressure drop. The allowable pressure drop defines the maximum flow rate through a single microchannel and economics drives the design towards this flow rate. Typically the flow rate in the microchannel is in laminar flow regime (Re < 2000) due to smaller hydraulic diameter. The laminar flow heat transfer in a smooth microchannel is limited by the boundary layer thickness. Commonly the hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The performance was also found to depend strongly on the geometric details of the roughness elements. Arora et al (2007) investigated wall features that create stable disrupted flow and break the laminar boundary layer in a microchannel over a wide range of flow rates. Experiments with gas flow with and without wall features showed that heat transfer increase is 20-80% more compared to the pressure drop increase in the laminar regime.…”
Section: Frontiers In Heat and Mass Transfermentioning
confidence: 99%
“…The performance was also found to depend strongly on the geometric details of the roughness elements. Arora et al (2007) investigated wall features that create stable disrupted flow and break the laminar boundary layer in a microchannel over a wide range of flow rates. Experiments with gas flow with and without wall features showed that heat transfer increase is 20-80% more compared to the pressure drop increase in the laminar regime.…”
Section: Frontiers In Heat and Mass Transfermentioning
confidence: 99%